2005
DOI: 10.1038/nn1575
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of moral character modulate the neural systems of reward during the trust game

Abstract: Studies of reward learning have implicated the striatum as part of a neural circuit that guides and adjusts future behavior on the basis of reward feedback. Here we investigate whether prior social and moral information about potential trading partners affects this neural circuitry. Participants made risky choices about whether to trust hypothetical trading partners after having read vivid descriptions of life events indicating praiseworthy, neutral or suspect moral character. Despite equivalent reinforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
597
4
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 637 publications
(682 citation statements)
references
References 45 publications
56
597
4
9
Order By: Relevance
“…It is unlikely that many participants approached this task believing the person they saw was an active participant due to the rather dated nature of the photographs. However, people do appear to easily anthropomorphize when stimuli behave like real people (Blakemore & Decety, 2001), and more pointedly, the pattern of behavior that we observed is similar to all other reported versions of the repeated Trust Game (Delgado et al, 2005;King-Casas et al, 2005;Krueger et al, 2007). We interpret this to mean that people approached the task at least ''as if" they were playing with a real life partner.…”
Section: Behavioral Measures Of Trustsupporting
confidence: 83%
See 4 more Smart Citations
“…It is unlikely that many participants approached this task believing the person they saw was an active participant due to the rather dated nature of the photographs. However, people do appear to easily anthropomorphize when stimuli behave like real people (Blakemore & Decety, 2001), and more pointedly, the pattern of behavior that we observed is similar to all other reported versions of the repeated Trust Game (Delgado et al, 2005;King-Casas et al, 2005;Krueger et al, 2007). We interpret this to mean that people approached the task at least ''as if" they were playing with a real life partner.…”
Section: Behavioral Measures Of Trustsupporting
confidence: 83%
“…Previous research has reported that both initial impressions (Delgado et al, 2005;van 't Wout & Sanfey, 2008) and direct experience (King-Casas et al, 2005;Singer et al, 2004) play important roles in influencing judgments of trustworthiness. This experiment provides the first account of how these variables interact in a social interactive financial investment game that has been explicitly designed to study trust (Berg et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations